Features of the monetary policy of the European Central Bank - Abdinabieva Gulnoza Shavkat kizi (Genius Journals, 2024)
This article presents a comprehensive analysis monetary policy adopted by the European Central Bank (ECB). Through a detailed analysis of the literature, the methods used and the subsequent results, the article aims to shed light on the key features of the ECB's approach to maintaining price stability and stimulating economic growth. The discussion covers a variety of tools and strategies, including interest rates, open market operations, and unconventional measures such as quantitative easing. The implications of these policies for economic stability are also discussed, followed by conclusions and suggestions for future consideration
Keywords: Monetary policy; European Central Bank; interest rates